ANALISIS PROSEDUR PEMBENTUKAN DAN HASIL YANG DICAPAI DALAM PERATURAN DESA TENTANG PERTUMBUHAN DESA - Ismia Nur Aurelia; Suharno Suharno; Dika Yudanto (Jurnal Inovasi Penelitian, 2022)
This study discusses village regulations for village development as the basis for village growth, in this case testing the suitability of the guidelines from Regional Regulation regarding the procedures for their formation dan implementation and the result achieved in Village Administration by the Village Head. Based on this, the legal problem that will be studied is how the procedure for establishing and the results achieved from village regulations regarding village growth arise in Ngringo Village. This writing uses empirical research methods carried out through documentation studies and direct interviews with the Ngringo Village Government. In 2021 it will produce two legal products as well as various develompents proclaimed through the Village Regulations that are formed that can be implemented well but not optimally.